2019
DOI: 10.23950/1812-2892-jcmk-00676
|View full text |Cite
|
Sign up to set email alerts
|

The clinical outcome comparison of ischemic stroke with and without atrial fibrillation

Abstract: Background: Atrial fibrillation increases the risk of stroke and is associated with poor stroke outcomes. The primary concern of this study was to compare the clinical outcome of ischemic stroke patients with atrial fibrillation and without atrial fibrillation.Methods: This was a retrospective cohort study using secondary data from electronic medical record and electronic stroke registry of Bethesda Hospital Yogyakarta, Indonesia. The data was collected from 2017-2018. The presence of atrial fibrillation at st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The prevalence of AF in our study was found to be 18.4%, further affirming its role as one of the leading causes of cerebral infarction and transient ischemic attack (TIA) according to the TOAST classification [13]. This rate is relatively high when compared to other studies conducted in Vietnam and Southeast Asian countries such as Thailand, Malaysia, Singapore, and Indonesia [3][4][5][6][7]. However, the mean age and male predominance observed in our study were comparable to these aforementioned studies.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The prevalence of AF in our study was found to be 18.4%, further affirming its role as one of the leading causes of cerebral infarction and transient ischemic attack (TIA) according to the TOAST classification [13]. This rate is relatively high when compared to other studies conducted in Vietnam and Southeast Asian countries such as Thailand, Malaysia, Singapore, and Indonesia [3][4][5][6][7]. However, the mean age and male predominance observed in our study were comparable to these aforementioned studies.…”
Section: Discussionsupporting
confidence: 76%
“…Studies in Western countries in patients with TIA/ischemic stroke report an AF prevalence ranging between 20.4% and 33.4% [2]. Meanwhile, studies in Southeast Asia recorded an AF rate in a lower range from 5.8% to 23.4% [3][4][5][6][7]. Therefore, screening for AF plays an essential role in the primary and secondary prevention of stroke.…”
Section: Introductionmentioning
confidence: 99%